Role of edible insects in food security and livelihoods in Mumbwa District, Central Province, Zambia - Nyawali, John (University of the Witwatersrand, Johannesburg, 2025)
The need to find sustainable sources of food and livelihoods is one of the agendas of many societies. This is in response to an increase in global population and increasing number of hungry people globally. The threat of increasing food insecurity, especially in poor communities of sub-Saharan Africa, entails the need to find sustainable alternative sources of nutrition alongside conventional agriculture and food systems. The use of edible insects is seen as having potential to help bridge nutritional and food insecurity gaps as they are a good source of protein and could be part of resilient and sustainable food systems. Edible insects have also been part of cultural dietary practices in Africa for thousands of years. However, despite these advantages, the use of edible insects as food has declined in recent decades in many African communities that were previously known to have high consumption. This study examined the degree of acceptability of edible insects and their contribution to household food security and livelihoods in rural communities in Mumbwa district of Central Province, Zambia. A mixed method research strategy was used across four administrative zones of the study area to collect data through questionnaires, observation and focus group discussions with adult participants (18 years and above). Ethnographic observations were also made on how rural residents engage and utilize edible insects as a resource, including how they find, harvest and prepare insects from natural settings. Results show that the majority (68%) of surveyed households consumed edible insects. This is attributed to the fact that entomophagy forms part of the food culture of the dominant local Kaonde ethnic group. Edible insects were also used as a means to promote social cohesion and cultural values. Edible insects were also a source of livelihood for 26% of respondents, with income from the sale of edible insects being similar to the total income generated from agricultural activities for the majority of households in the community. It was reported that the income generated from the sale of insects, especially caterpillars, was much higher than maize, as a 5-litre bucket of caterpillars sells for around K300 (about US$11) during the harvest season and K500 (about $19) in the off season. In some cases, the income was higher depending on the type and quantity of the caterpillar species being sold while the same quantity of maize grain sold for K20 ($0.75) during harvest season (June–August) and K50 ($2) off season (October until the next harvest season). This means that trade in edible insects could help mitigate poverty among rural households. Impediments to the utilization of edible insects as a source of livelihood include the reduction in insect population and availability, lack of infrastructure to promote trade, and lack of environmental stewardship to enhance ecosystems protection. Reduced availability of insects in this community was attributed to climate change, habitat destruction and lack of effective management. To ensure sustainable livelihoods and food security in rural communities, there is need to maintain ecosystems in good condition as well as recognizing edible insects as finite valuable resources that should be managed. This requires adequate infrastructure and public policy cutting across socioeconomic, health, education and trade/business systems. Better governance and coordination across different actors involving edible insects as a form of natural capital can help achieve various Sustainable Development Goals of relevance to rural African communities.
A research thesis submitted in fulfillment of the requirements for the award of the degree of Doctor of Philosophy, to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2025
Keywords: Food security; Livelihoods; Sustainability; Edible insects; Ecosystem services; Acculturation; Entomophagy; UCTD; SDG-2: Zero hunger; SDG-11: Sustainable cities and communities